A Review on Electromagnetics (EM) Exposure Measurement Techniques from Base Station - Roslan, Umar; Mohd Khairul Amri, Kamarudin; Siti Nur Dianah, Abdul Rahman; Nor Hazmin, Sabri; A.N, Dagang (2017)
EM exposure in the range of non-ionizing radiations (NIR) which falls in the radio frequency up to 3GHz is mainly sourced from mobile phone base stations, broadcast towers and radar facilities. This reviews based on previous researcher obtained results and methods in order to determine the best technique to measure the exposure. Moreover, the estimation of exposure levels by considering the specification of the antennas installed and area of the base stations itself was also reviewed. It was found that numerous study of NIR exposure level has been conducted in other countries,while Malaysia has become aware of the importance. Most of the studies used field meter to carry out the measurement, and the exposure level obtained were far lower than the limit recommended by World Health Organization (WHO).